2010
DOI: 10.1097/psy.0b013e3181c484dc
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Socioeconomic Status and Presence of the Metabolic Syndrome in Midlife Community Volunteers

Abstract: OBJECTIVE-Objective indices of socioeconomic status (SES) predict diverse sources of morbidity and mortality, as well as numerous biological and behavioral risk factors for disease. Here we examine whether subjective SES may be similarly associated with measured risk factors, including the metabolic syndrome and its components of elevated blood pressure, high fasting glucose, dyslipidemia, and central adiposity. METHODS-Observationswere based on a community sample of 981 adults (30-54 years of age; 52% female;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 45 publications
2
107
1
1
Order By: Relevance
“…Indirect effects of SSS on initial memory through physical health variables (i.e., chronic disease burden and stroke) are in line with a growing body of observational and experimental evidence that low SSS elevates multiple biological risk factors for disease, including higher resting heart rate, higher blood pressure, reduced beta adrenergic receptor function, higher body mass index, altered cortisol responses, angina, reduced immune defense, lower high-density lipoprotein cholesterol, impaired glucose tolerance, and elevated interleukin-6 [8, 33, 34]. It should be noted that the self-reported physical health variables used in this study are unlikely to fully capture all of the stress-related biological risk factors that have been linked to low SSS.…”
Section: Discussionmentioning
confidence: 87%
“…Indirect effects of SSS on initial memory through physical health variables (i.e., chronic disease burden and stroke) are in line with a growing body of observational and experimental evidence that low SSS elevates multiple biological risk factors for disease, including higher resting heart rate, higher blood pressure, reduced beta adrenergic receptor function, higher body mass index, altered cortisol responses, angina, reduced immune defense, lower high-density lipoprotein cholesterol, impaired glucose tolerance, and elevated interleukin-6 [8, 33, 34]. It should be noted that the self-reported physical health variables used in this study are unlikely to fully capture all of the stress-related biological risk factors that have been linked to low SSS.…”
Section: Discussionmentioning
confidence: 87%
“…There is promising stress research on the metabolic syndrome, which is commonly defined as having at least three risk factors among central obesity, hypertension, hyperglycemia, elevated triglycerides, and low levels of high-density lipoprotein (HDL) cholesterol, although other definitions are also available (2,34,78). Early studies of chronic exposure to stress, operationalized as socioeconomic status (SES), showed lower SES to be associated with increased risk of the metabolic syndrome (9); this finding has been replicated in a variety of different populations (65,69,82,87) with the temporal order between exposure and outcome confirmed by cross-lagged analyses (22). Analyses of other stressors, such as loneliness (118), marital stress (in women but not men) (119), and workplace stress (14), have also found a longitudinal association with the onset of the metabolic syndrome, even after controlling for SES.…”
Section: Population-level Mechanistic Studiesmentioning
confidence: 91%
“…10 Using these ladders, relationships have been demonstrated between SSS and a range of adult health outcomes, particularly for non-Hispanic white populations. [11][12][13] These relationships are often stronger than those with objective SES measures. 5,6,[11][12][13][14][15][16][17][18] Although SSS is associated with adolescent health outcomes, these associations seem weaker and less consistent than those demonstrated in adults.…”
Section: What This Study Addsmentioning
confidence: 98%
“…[11][12][13] These relationships are often stronger than those with objective SES measures. 5,6,[11][12][13][14][15][16][17][18] Although SSS is associated with adolescent health outcomes, these associations seem weaker and less consistent than those demonstrated in adults. 2,3,[18][19][20][21][22][23][24][25][26][27][28] These developmental discrepancies suggest adolescence is a key period in the formation of an individual's SSS.…”
Section: What This Study Addsmentioning
confidence: 98%